The - Bronmark, Chister (Oxford University Press, 1998)
Today scientists are increasingly applying modern and evolutionary theory to the understanding of freshwater ecosystems. Taking note of this trend, authors Bronmark and Hansson have compiled a comprehensive overview that summarizes these new approaches and integrates them with more traditional limnology. The result is a comprehensive, accessible resource that fully explores of the evolution of freshwater organisms, the importance of biotic interactions--including competition, predation, parasitism, and symbiosis--and community level processes such as food web interactions. The authors have also included a chapter on conservation that identifies the threats posed by human activity and possible counteractive measures